247 Virtual community and partner-engaged panels - We can do them, but should we? - Lesli Skolarus; Tamara Sutton; Darius Tandon; Josefina Serrato (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: We describe the transition of ShAred Resource Panels (ShARPs) within the Center for Community Health (CCH) at Northwestern University’s Clinical and Translational Sciences (NUCATS) Institute to virtual sessions and explore ongoing practices. METHODS/STUDY POPULATION: Restrictions placed during the COVID-19 pandemic led to changes in community-engaged health equity research, such as the transition of community and partner-engaged panels from in-person to virtual. ShARPs have occurred since December 2015. The model includes research team members, community members, community co-facilitator, and CCH staff. These custom panels bring together 8-10 community members familiar with a research topic or community of focus, offering feedback on adaptations that can improve research relevance and feasibility. Until the COVID-19 pandemic, all ShARPs were conducted in person. From March 2020 to January 2023, panels occurred virtually. From 2023, the option of virtual or in-person ShARPs has been available. Count data and informal interview data were reviewed. RESULTS/ANTICIPATED RESULTS: The number of ShARPs peaked in 2019 and has remained stable. The first virtual ShARP occurred on April 22, 2020, and all subsequent sessions have been virtual. As of October 2023, 6 ShARPs have occurred, with no research teams pursuing an in-person session despite its availability. Participants described virtual ShARPs as convenient and accessible. Academic teams cited concern about low community member participation should they opt for an in-person session. DISCUSSION/SIGNIFICANCE: It is feasible to conduct ShARPs virtually and is the current preferred modality. Whether virtual ShARPs enhance, neutralize, or detract from the effectiveness of the session is unknown and guides our future work. More research is needed, including discussion, and learning from our CTSA colleagues.